2019
DOI: 10.1371/journal.pone.0211707
|View full text |Cite
|
Sign up to set email alerts
|

Effects of playing position, pitch location, opposition ability and team ability on the technical performance of elite soccer players in different score line states

Abstract: The purpose of this study was to investigate the effects of playing position, pitch location, team ability and opposition ability on technical performance variables (pass, cross, corner, free kick accuracy) of English Premier League Soccer players in difference score line states. A validated automatic tracking system (Venatrack) was used to code player actions in real time for passing accuracy, cross accuracy, corner accuracy and free kick accuracy. In total 376 of the 380 games played during the 2011–12 Engli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 40 publications
(138 reference statements)
2
21
0
3
Order By: Relevance
“…Perhaps as a consequence, losers experienced significantly less player possessions in defense but also in midfield. Moreover, psychological factors that may impact a player's performance on a losing team need to be considered as researchers have recently suggested that if the outcome of a match is known in the second half due to superior opposition or a perceived unsurmountable lead, then player motivation may decline and potentially result in a decrease in work rate and reduced effort attempting to regain possession [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps as a consequence, losers experienced significantly less player possessions in defense but also in midfield. Moreover, psychological factors that may impact a player's performance on a losing team need to be considered as researchers have recently suggested that if the outcome of a match is known in the second half due to superior opposition or a perceived unsurmountable lead, then player motivation may decline and potentially result in a decrease in work rate and reduced effort attempting to regain possession [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, researchers indicate a number of other determinants of players’ activity during a match, including quality of opposition ( Bilek and Ulas, 2019 ), team and opposition ability ( Redwood-Brown et al, 2019 ), team formation ( Aquino et al, 2020 ), match status ( Gonzalez Rodenas et al, 2019 ), players’ age and experience ( Lorenzo-Martínez et al, 2019 ), and climate conditions ( Coker et al, 2020 ). However, during a soccer match, players experience all these factors simultaneously, which is why modern studies focus on multifactorial analyses, using advanced statistical methods ( Moura et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The increased accessibility of detailed match data is largely due to the progression made in semi-and fully-automated tracking [1][2][3][4]. Noticeably, the technical and tactical match performance of professional soccer players, has been shown to be affected by several different contextual, situational and positional attributes [5][6][7][8][9][10]. Thus, the continuous movement dynamic and the corresponding Sensors 2020, 20, 3213 2 of 13 movement within the context of the match produces thousands of different values that reflect in total what the player, players, team or teams do together as a whole during the game.…”
Section: Introductionmentioning
confidence: 99%